The relationship between the development of freight forwarding organization and export-import activity and it’s impact on the economics development of Bangladesh - Mia, Md.Tusher (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.